Simple Syntheses of New Pegylated Trehalose Derivatives as a Chemical Tool for Potential Evaluation of Cryoprotectant Effects on Cell Membrane - Pomeisl, Karel; Richter, Jan; Golan, Martin; Kratochvílová, Irena (Molecules (Basel, Switzerland), 2020)
In our work, we developed the synthesis of new polyfunctional pegylated trehalose derivatives and evaluated their cryoprotective effect using flow cytometry. We showed that new compounds (modified trehaloses) bound to appropriate extracellular polymeric cryoprotectants could be helpful as a chemical tool for the evaluation of their potential toxic cell membrane influences. Our aim was to form a chemical tool for the evaluation of cryoprotectant cell membrane influences, which are still not easily predicted during the freezing/thawing process. We combined two basic cryoprotectants: polyethyleneglycols (PEGs) and trehalose in the new chemical compounds-pegylated trehalose hybrids. If PEG and trehalose are chemically bound and trehalose is adsorbed on the cell surface PEGs molecules which are, due to the chemical bonding with trehalose, close to the cell surface, can remove the cell surface hydration layer which destabilizes the cell membrane. This was confirmed by the comparison of new material, PEG, trehalose, and their mixture cryoprotective capabilities.
Keywords: zmrazování; cryoprotection; Trehalose; polyethylenglykoly; viabilita buněk; Click Chemistry; kryoprotektivní látky; pegylation; Humans; buněčná membrána; trehalosa; Cryoprotective Agents; Polyethylene Glycols; click chemie; kryoprezervace; Cell Line, Tumor; Flow Cytometry; nádorové buněčné linie; Cryopreservation; click-chemistry; dimethylsulfoxid; Cell Membrane; Dimethyl Sulfoxide; průtoková cytometrie; Cell Survival; lidé; Freezing